2016
DOI: 10.1007/s11356-016-7189-9
|View full text |Cite
|
Sign up to set email alerts
|

Scale-up of electrolytic and photoelectrolytic processes for water reclaiming: a preliminary study

Abstract: This work focuses on the scale-up of electrochemical and photoelectrochemical oxidation processes with diamond anodes for the removal of organic pollutants and disinfection of treated urban wastewater, two of the most important parameters for the reclaiming of wastewater. The removal of organics was studied with actual biologically treated urban wastewater intensified with 100 mg dm(-3) of caffeine, added as a trace organic pollutant. The disinfection was also studied with biologically treated urban wastewater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 45 publications
1
6
0
Order By: Relevance
“…Additionally, the decrease of TOC concentration seems to indicate that the depletion of any organic may occur-most likely, carboxylic or methyl As can be observed, the partial oxidation of AMX and AMP depends on the technology used. As expected [26,34,35], photolysis is not able to completely remove the antibiotics, and around 70% of AMX and AMP remains unaltered in the solutions after 8 h of treatment. Moreover, in sulphate media, the removal trends of both compounds are almost overlapping, but they differ significantly in chlorine media, in which the degradation of AMP is slower.…”
Section: Resultssupporting
confidence: 63%
See 2 more Smart Citations
“…Additionally, the decrease of TOC concentration seems to indicate that the depletion of any organic may occur-most likely, carboxylic or methyl As can be observed, the partial oxidation of AMX and AMP depends on the technology used. As expected [26,34,35], photolysis is not able to completely remove the antibiotics, and around 70% of AMX and AMP remains unaltered in the solutions after 8 h of treatment. Moreover, in sulphate media, the removal trends of both compounds are almost overlapping, but they differ significantly in chlorine media, in which the degradation of AMP is slower.…”
Section: Resultssupporting
confidence: 63%
“…The formation of these species is promoted at high current density [26,34,35], but it is not always reflected by a more efficient degradation. In fact, in light of the results obtained in this study, the transformation of AMP and AMX is favored at high current densities, but not their full mineralization.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, commercial reactors such as DiaCell® cell, equipped with a BDD anode, SS cathode and a UV irradiation source, has been successfully used for the disinfection of an E. coli contaminated real secondary effluent. This study revealed an improvement of four times the inactivation rate when compared to a single electrolysis approach in which the main inactivation mechanism consisted on the indirect oxidation in the bulk solution by means of photo-activated species derived from active chlorine ( Martín de Vidales et al., 2016 ).…”
Section: Indirect Oxidationmentioning
confidence: 96%
“…When electrochemical oxidation processes and UV light are not considered to be simultaneously operating at the electrode-solution interphase, and rather complementing each other’s effect in a synergistic way, indirect disinfection processes using highly electro-catalytic and non-photoactive electrodes have been shown to be effective approaches. Under this perspective, it must be noted that UV irradiation represents a highly effective disinfection method that, although costly, can be combined with other disinfection procedures such as electrochemical oxidation ( Cotillas et al., 2016a ; Haaken et al., 2013 ; Martín de Vidales et al., 2016 ; Singla et al., 2020 ). The electrodes employed in this type of processes are usually the DSA, MMO or BDD electrodes ( Panizza and Cerisola, 2005 , 2009 ).…”
Section: Indirect Oxidationmentioning
confidence: 99%